Koersi dan Seduksi: Dinamika Komunikasi Gerakan Tarbiyah dalam Pembentukan Loyalitas Kader Lembaga Dakwah Kampus di Era Kontemporer - Andi Fakhrullah; Andi Faisal Bakti; Syamsul Yakin (Ad-DA'WAH, 2026)
This study analyzes the dynamics of communication within the Tarbiyah Movement in shaping the loyalty of cadres at the Campus Da'wah Institute (LDK) of UIN Syarif Hidayatullah Jakarta. Amidst a heterogeneous and moderate student demographic, this movement has succeeded in building a militant cadre base. Using a qualitative approach with a phenomenological design, this study dissects the interactive experiences of da'wah activists through the lens of Active Acceptance theory and the concept of Coerseduction. The findings show that loyalty is formed through a strategic dialectic between coercion and seduction. During the recruitment phase, seduction strategies dominate by offering discourses of piety, brotherhood, and an image of excellence as a panacea for students' culture shock. Conversely, during the cadre maintenance phase, coercion strategies operate through organizational discipline legitimized by sharia authority, thereby constructing obedience as an absolute theological mandate. This study concludes that the loyalty of LDK cadres is not merely the result of passive indoctrination, but rather a negotiation of meaning in which the fulfillment of affective needs through persuasion and ideological binding through theological pressure work simultaneously.